The pathological significance and potential mechanism of ACLY in cholangiocarcinoma - Sun, Xiaoyan; Zhao, Xiaofang; Wang, Senyan; Liu, Qi; Wei, Wenjuan; Xu, Jing; Wang, Hongyang; Yang, Wen (Frontiers in Immunology, 2024)
Background and aim Cholangiocarcinoma (CCA) is a rare cancer, yet its incidence and mortality rates have been steadily increasing globally over the past few decades. Currently, there are no effective targeted treatment strategies available for patients. ACLY (ATP Citrate Lyase), a key enzyme in de novo lipogenesis, is aberrantly expressed in several tumors and is associated with malignant progression. However, its role and mechanisms in CCA have not yet been elucidated. Methods The expression of ACLY in CCA was assessed using transcriptomic profiles and tissue microarrays. Kaplan-Meier curves were employed to evaluate the prognostic significance of ACLY in CCA. Functional enrichment analysis was used to explore the potential mechanisms of ACLY in CCA. A series of assays were conducted to examine the effects of ACLY on the proliferation and migration of CCA cells. Ferroptosis inducers and inhibitors, along with lipid peroxide probes and MDA assay kits, were utilized to explore the role of ACLY in ferroptosis within CCA. Additionally, lipid-depleted fetal bovine serum and several fatty acids were used to evaluate the impact of fatty acids on ferroptosis induced by ACLY inhibition. Correlation analyses were performed to elucidate the relationship between ACLY and tumor stemness as well as tumor microenvironment. Results The expression of ACLY was found to be higher in CCA tissues compared to adjacent normal tissues. Patients with elevated ACLY expression demonstrated poorer overall survival outcomes. ACLY were closed associated with fatty acid metabolism and tumor-initiating cells. Knockdown of ACLY did not significantly impact the proliferation and migration of CCA cells. However, ACLY inhibition led to increased accumulation of lipid peroxides and enhanced sensitivity of CCA cells to ferroptosis inducers. Polyunsaturated fatty acids were observed to inhibit the proliferation of ACLY-knockdown cells; nonetheless, this inhibitory effect was diminished when the cells were cultured in medium supplemented with lipid-depleted fetal bovine serum. Additionally, ACLY expression was negatively correlated with immune cell infiltration and immune scores in CCA. Conclusion ACLY promotes ferroptosis by disrupting the balance of saturated and unsaturated fatty acids. ACLY may therefore serve as a potential diagnostic and therapeutic target for CCA.